Man’s Impact on the Coastline - Evans, Graham (Journal of Iberian Geology, 2008)
The coastline is important to man as a site of settlement, commercial, industrial and leisure activity and is likely to be important for the production of energy in the future. It has been greatly affected by human activity. Coastal protection schemes, stabilisation of channels in estuaries and on deltas, reclamation and urbanisation have produced profound changes, often with unexpected results. Also, human activities in the drainage basins of the adjacent hinterland have had important consequences on the coasts by influencing the supply of sediment, nutrient and pollutants. Climatic and sea level changes are likely to greatly affect this vulnerable zone in the future.